Измерения массы, плотности и вязкости - Кузьмин В. Я. Виктор Яковлевич; Торопин С. И. Сергей Иванович; Тарбеев Ю. В. Юрий Васильевич; Павлов И. В. Игорь Всеволодович; Перельман Е. И. Евгений Ильич; Тютикова М. И. Мария Ивановна; Любомиров А. Б. Андрей Борисович; Домостроева Н. Г. Наталья Григорьевна; Коноплева Г. П. Галина Павловна (Москва, Изд-во стандартов, 1988)
Авт. указ. на обороте тит. л.